EKSISTENSI OTONOMI DESA PAKRAMAN DI BALI DALAM KERANGKA OTONOMI DAERAH KHUSUSNYA DALAM PENGELOLAAN OBYEK WISATA - Ariani, I Gusti Ayu Agung (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 2 (2014), 2014)
Traditional village (Pakraman) is an indigenous people who have the authority to manage his own household, and the authority was born out of the village so it is often referred to as having genuine autonomy. On the other hand with the establishment of the state covering the entire area of the country where the indigenous villages were then raised the issue regarding the implementation of autonomy in relation to the traditional village authorities also state that gives autonomy to the region in accordance with the centralized system that was followed. That's why it is necessary to examine the existence of a traditional village in Bali autonomy within the framework of regional autonomy especially in tourist object  management. This study were classified in empirical legal research can be seen in the study area were selected using purposive sampling method, it can be seen that initially the traditional village autonomy is not recognized in the context of managing a tourist object because of the traditional village is not at all involved in the management of tourist objects. It was only through an uphill battle, even with through demonstrations, traditional village involved in the management of a tourist attraction. In the original development management involving private parties as well as third party, then is only managed as a form of cooperation between local government and the Desa Pakraman only somewhat proportional outcomes assessed, although there are groups of people who do not approve even sueing Bendesa Desa Pakraman. The cooperation in tourism management proficiency level set forth in a letter of the Collective Agreement between the Government and Bendesa Desa Pakraman.
Keywords: existence; indigenous village autonomy; regional autonomy